Gender Responsive Climate Financing as a Strategy to Climate Change Mitigation and Adaptation: a Legal Analysis. - Kabaseke, Charlotte (Kabale University, 2023)
Women have been noted to be key contributors in seeking strategies to mitigation and adaptation in respect to climate change. Research has acknowledged that due to women’s socially constructed gender roles, enhancing their access to economic and social resources is a key contributor to the promotion of better mitigation and adaptation outcomes. It has, however, been observed that despite this realization, climate finances are usually unequally distributed and with unequal participation of men and women during the distribution or consideration for distribution. The available research has, however, not adequately analyzed the role of law in ensuring that equal distribution is achieved. It is therefore important for the barriers against women’s equal access to climate finance to be eliminated, from a legal perspective. Although various strategies have been developed for ensuring the realization of climate finance, there is need to legally strengthen the financing through more gender-equitable ways. This article therefore employs the doctrinal research method to analyze the adequacy of the existing climate change legal framework in ensuring equal distribution of climate finance with respect to women. The article also analyzes a few of the non-legal factors that are contributors to the unequal distribution of climate finance. The article concludes that legal recognition of equitable climate finance distribution will go a long way in contributing to the realization of climate change mitigation and adaptation. In addition, the chapter makes recommendations on improved ways of ensuring equitable distribution of climate finance.